Conformational isomerism breaks the electrolyte solubility limit and stabilizes 4.9 V Ni-rich layered cathodes - Ziyang Lu; Huijun Yang; Jianming Sun; Jun Okagaki; Yoongkee Choe; Eunjoo Yoo (Nature Communications)
Abstract By simply increasing the concentration of electrolytes, both aqueous and non-aqueous batteries deliver technical superiority in various properties such as high-voltage operation, electrode stability and safety performance. However, the development of this strategy has encountered a bottleneck due to the limitation of the intrinsic solubility, and its comprehensive performance has reached its limit. Here we demonstrate that the conformational isomerism of the solvent would significantly affect the solubility of electrolytes. By transforming the configuration of solvent from cis-cis to cis-trans upon thermal triggering, we successfully break the solubility limit, and a beyond concentrated electrolyte with the lowest solvent-to-salt molar ratio of 0.70 is constructed. Transitions between cis-cis and cis-trans conformers are observed through Nuclear Magnetic Resonance (NMR) testing. The electrolyte consists entirely of anion-mediated solvation structures and promotes the formation of robust inorganic-dominated cathode electrolyte interphase. As a result, it enables stable cycling of 4.9 V-class LiNi0.8Co0.1Mn0.1O2 positive electrodes. Moreover, a high capacity of 151.2 mAh g−1 can be maintained after 1000 cycles at cut-off voltage of 4.8 V. This work provides a chemical pathway to build new concept electrolytes working under harsh conditions.